Twilight of democracy : the seductive lure of authoritarianism - Applebaum, Anne (New York : Doubleday, 2020)
A Pulitzer Prize-winning historian and journalist explains, with electrifying clarity, why some of her contemporaries have abandoned liberal democratic ideals in favor of strongman cults, nationalist movements, or one-party states. Across the world today, from the U.S. to Europe and beyond, liberal democracy is under siege while different forms of authoritarianism are on the rise. In Twilight of Democracy, prize-winning historian Anne Applebaum argues that we should not be surprised by this change: There is an inherent appeal to political systems with radically simple beliefs, especially when they benefit the loyal to the exclusion of everyone else. People are not just ideological, she contends in this captivating extended essay; they are also practical, pragmatic, opportunist. The authoritarian and nationalist parties that have arisen within modern democracies offer new paths to wealth or power for their adherents. Describing politicians, journalists, intellectuals, and others who have abandoned democratic ideals in the UK, U.S., Spain, Poland, and Hungary, Applebaum reveals the patterns that link the new advocates of illiberalism and charts how they use conspiracy theory, political polarization, social media, and nostalgia to change their societies
Incluye referencias bibliográficas
Keywords: S. XXI; Autoritarismo; Democracia; Partido nacionalista; Populismo